Predictive value in academic performance of learning strategies, academic goals, educational styles and parental expectations in ESO - Suárez Valenzuela, Sara; Suárez Riveiro, José Manuel (Revista Complutense de Educación, 2023)
Cognitive, motivational and social factors are related to the research of learning processes. Together, they affect the achievement of the best academic results. This work aims to study the predictive value in academic performance of learning strategies, goals, educational styles and parental academic expectations in secondary school. In a novel way, the mutual perceptions of students and parents about these variables are incorporated. To this end, a quantitative, descriptive, correlational and inferential study was carried out. Four questionnaires were administered to a sample of 358 students between the ages of 11 and 17 from a public ESO Center. The parental version of the same instruments was used with 158 mothers and fathers from the same school. The regression analysis results show that 62.5% of the performance variance is explained by five variables: Perceived parental expectation, Effort regulation, Perceived ego overcoming goal, Perceived negative ego protection goal, and Perceived permissive style. Student´s profile who achieves the best academic results adequately self-regulates the effort required to acquire knowledge, perceives high parental academic expectations, are perceived as having performance goals, and their family environment is mainly affective. This article concludes with some recommendations to be considered in educational practice such as, reinforcing parental guidance and/or training in ESO, and influencing strategic and motivational aspects of students.
Keywords: learning strategies; academic goals; parenting educational styles; parental academic expectations; academic performance